A High‐Voltage, Dendrite‐Free, and Durable Zn–Graphite Battery. Issue 4 (1st December 2019) - Wang, Gang; Kohn, Benjamin; Scheler, Ulrich; Wang, Faxing; Oswald, Steffen; Löffler, Markus; Tan, Deming; Zhang, Panpan; Zhang, Jian; Feng, Xinliang
Abstract: The intrinsic advantages of metallic Zn, like high theoretical capacity (820 mAh g −1 ), high abundance, low toxicity, and high safety have driven the recent booming development of rechargeable Zn batteries. However, the lack of high‐voltage electrolyte and cathode materials restricts the cell voltage mostly to below 2 V. Moreover, dendrite formation and the poor rechargeability of the Zn anode hinder the long‐term operation of Zn batteries. Here a high‐voltage and durable Zn–graphite battery, which is enabled by a LiPF6 ‐containing hybrid electrolyte, is reported. The presence of LiPF6 efficiently suppresses the anodic oxidation of Zn electrolyte and leads to a super‐wide electrochemical stability window of 4 V (vs Zn/Zn 2+ ). Both dendrite‐free Zn plating/stripping and reversible dual‐anion intercalation into the graphite cathode are realized in the hybrid electrolyte. The resultant Zn–graphite battery performs stably at a high voltage of 2.8 V with a record midpoint discharge voltage of 2.2 V. After 2000 cycles at a high charge–discharge rate, high capacity retention of 97.5% is achieved with ≈100% Coulombic efficiency. Abstract : A high‐voltage and durable Zn–graphite battery is reported, which is enabled by a LiPF6 ‐containing hybrid electrolyte. The battery can perform at a high voltage of 2.8 V and output a record midpoint discharge voltage of 2.2 V. High rate capability (charge within 3 min) and long‐term cycling stability (>97% capacity retention after 2000 cycles) are also achieved.